From Then to now: Diversity, Equity, and Inclusion in the Association of Southeastern Biologists - Hays, Kimberly A.; Havran, J. Christopher; Heard, Matthew J.; Morris, Ashley B.; Ovueraye, Loretta (Frontiers in Sociology, 2021)
The Association of Southeastern Biologists was founded in 1937 with the goal of increasing the contact and collaboration between scientists in the southeastern United States (US). With the exception of two years during World War II and one year during the COVID-19 pandemic, the Association has met annually to promote research and education in the biological sciences by providing a student-friendly networking environment. In recent years, the Association has placed an increased focus on diversity, equity, and inclusion among elected and appointed leaders, among participants in the annual meeting, and in the development of funding and other opportunities for students. This work prompted us to review the history of our Association, including periods of racial segregation and inequity, and focus on our current efforts to promote access and inclusion by students and scientists from myriad underrepresented groups. In so doing, the past provides us with the opportunity to cast a vision for the future of the Association. In this paper, we seek to share the journey of the Association of Southeastern Biologists in this regard so that we may be transparent, exposing the missteps and amplifying the successes of our organization. We envision this work as a first step toward creating a more open and inclusive scientific community for the future.